In-situ ionized construction of PVDF/sodium polyacrylate-grafted-PVDF blend ultrafiltration membrane with stable anti-oil-fouling ability for efficient oil-in-water emulsion separation - Gao, Shoujian; Liu, Pingping; Jin, Jian (Frontiers in Membrane Science and Technology, 2024)
Traditional polymeric membranes usually suffer from serious oil fouling and quick decline of water flux when separating oil-in-water emulsions. In this work, we report the fabrication of the sodium polyacrylate (PAAS) blended polyvinylidene fluoride (PVDF) ultrafiltration membrane which behaves hydrophilicity, underwater low-oil-adhesive superoleophobicity and outstanding anti-oilfouling ability even for viscous crude oil. The blend membrane was fabricated via a two-step method, including the nonsolvent-induced phase inversion of PVDF/polyacrylic acid-grafted-PVDF (PVDF/PAA-g-PVDF) blend membrane and the subsequent in-situ ionization of PAA into PAAS. The two-step method improves the affinity between the strong hydrophilic additive PAAS and the hydrophobic polymer matrix PVDF, thus endowing the blend membrane with long-term stable superwetting property for 1100 days. The PVDF/PAAS-g-PVDF blend membrane can efficiently separate multiple emulsifier-stabilized oil-in-water emulsions with ultrahigh separation efficiency of 99.97% (the residual oil content in the filtrate is lower than 3 ppm after one-step separation) and high water flux of 350 L m -2 h -1 bar -1 . The blend membrane also shows good cycling performance, and can be easily cleaned by water washing during several separation cycles of the crude oil-in-water emulsion. This work inspires a feasible route of fabricating stable anti-oil-fouling membranes for separation of emulsified oily water.